Change commitment in low-status merger partners: the role of information processing, relative ingroup prototypicality, and merger patterns - Rosa, M.; Kavanagh, E.; Kounov, P.; Jarosz, S.; Waldzus, S.; Collins, E. C.; Giessner, S. (British Journal of Social Psychology, 2017)
Merger announcements cause stress among employees, often leading to low change commitment, especially among employees from the lower-status merger partner. Such stress influences how deeply employees process merger-relevant information. Previous research examined how merger patterns that preserve versus change status differences impact merger support, but did not address how employees’ information processing may influence this relationship. The current research addresses this gap through a scenario experiment, focusing on the low-status merger partner. The interplay between merger patterns and information processing was examined regarding employees’ prototypicality claims in relation to merger support. Results suggest that an integration-equality merger pattern increases change commitment via prototypicality claims in the new organization, conditional to employees’ systematic information processing.